Make me say it again, girl [compact disc] - Beyoncé, 1981-; 2 Chainz, 1977-; Songz, Trey; Quavo, 1991-; Takeoff, 1994-2022; Snoop Dogg, 1972-; Ross, Rick, 1976-; DeBarge, El (BFD ; RI Top Ten Records, 2023)
The Isley Brothers are back with their first new full-length album in 16 years. The music icons collaborate with a long list of stars on this CD, including Beyonce, Snoop Dogg, Rick Ross, 2 Chainz, and more.